Technology trends in the creative and cultural industries sector: a systematic literature review - Luis Ortiz-Ospino; Estiven González-Sarmiento; Jhoselin Roa-Perez (Journal of Innovation and Entrepreneurship)
Abstract This article focuses on reviewing technology trends related to the creative and cultural industries (CCIs) and their impact on the development of cultural goods and services. Through a systematic literature review and a technology oversight process, the most influential global technology trends for CCIs are identified, with a specific focus on digital content. The results reveal that these technology trends are driving changes in the creation, the production, the distribution, and the consumption of digital content. On the demand side, there has been a significant increase in the consumption of digital content, fueled by improved access and technological efficiency. The pandemic has further accelerated this shift. On the supply side, CCIs have leveraged internet access and mobile devices to promote brands, deploy digital marketing strategies, and expand e-commerce. The study identifies key subsectors of CCIs in the digital content field, including audiovisual, design, editorial and publishing, music and entertainment, digital advertising, information technology, software, computer services, and video games. Finally, it highlights the key role of CCIs in the transition toward a more sustainable and socially responsible economy. This study provides valuable insights into the dynamics of CCIs and the technological trends reshaping this sector, fostering innovation and professionalization in the creative economy.